The utility of cardiovascular drugs in the treatment of cerebrovascular disease - Bösel, Julian; Amiri, Hemasse (Current opinion in investigational drugs, 2010)
Cardiovascular and cerebrovascular diseases share many pathophysiological traits, often impact one another and share several risk factors, though not always to the same magnitude. Therefore, it is not surprising that many classes of cardiovascular drugs have demonstrated effectiveness in the primary prevention, acute treatment and secondary prevention of stroke. Important advances have been made since 2007 in the use of antiplatelets, anticoagulants, antihypertensives, antiarrhythmics and statins for the treatment of stroke. This review summarizes selected clinical trials of cardiovascular drugs completed from 2007 to 2010 that generated important evidence supporting the efficacy of these drugs in stroke treatment. Ongoing trials and preclinical research of promising agents and treatment strategies are also discussed.
Gesehen am 01.02.2023